Предмет: Математика,
автор: valera231232233
2 1/4 : ( 6 - 3 3/8 • 1 1/3 )
Ответы
Автор ответа:
4
Ответ:
2 1/4 : (6 - 3 3/8 • 1 1/3) = 3 3/8 • 1 1/3 = 6 - 4 1/2 = 2 1/4 : 1 1/2 = 1 1/2
Автор ответа:
0
Ответ:
1 1/2
Пошаговое объяснение:
1) 3 3/8 • 1 1/3 = 27/8 *4/3 = 9/2 = 4 1/2
2) 6 - 4 1/2 = 5 2/2 - 4 1/2 = 1 1/2
3) 2 1/4 : 1 1/2 = 9/4 : 3/2 = 9/4 * 2/3 = 3/2= 1 1/2
Похожие вопросы
Предмет: Математика,
автор: marina777775
Предмет: Математика,
автор: lohnkb55
Предмет: Английский язык,
автор: pkt1m00n13
Предмет: Математика,
автор: elenanomad
Предмет: Математика,
автор: kamistarkamistar